Field Observation of Diurnal Dissolved Oxygen Fluctuations in Shallow Groundwater. Issue 3 (19th May 2014) - Schilling, Keith E.; Jacobson, Peter
Abstract Dissolved oxygen (DO) concentrations influence many biogeochemical processes in groundwater systems but studies of temporal variability in DO are lacking. In this study, we used an optical DO probe to measure rapid changes in concentration due to plant‐groundwater interaction at an alluvial aquifer field site in Iowa. Diurnal DO concentrations were observed during mid‐ to late‐summer when soil conditions were dry, fluctuating approximately 0.2 to 0.3 mg/L on a daily basis. DO fluctuations in groundwater were out‐of‐phase with diurnal water table fluctuations, increasing during the day and decreasing at night. DO consumption at night is likely due to increased soil autotrophic and heterotrophic respiration linked with patterns of carbon supply derived from daytime photosynthetic activity, and consistent with available literature on diurnal soil respiration patterns. Although more work is needed to quantify specific processes, our results indicate the potential usefulness of the new optical DO technology to reveal insights regarding many ecohydrological processes.